Penerapan Building Information Modeling (BIM) dalam Perencanaan Rumah Susun Kementerian Sosial BBRSPDF Kota Surakarta 6 Lantai - Wibowo, Aditya; Asha, Safia Nur; Nurdiana, Asri; Setiabudi, Bambang (Jurnal Sipil dan Arsitektur, 2023)
Construction planning and management is carried out as an attempts to find out various aspects that will be use in facilitating the construction, so it is following the applicable requirements, building functions, and economy. In construction projects, problems are often found at the planning stage or during construction, such as clashes between design elements or between schedules which can cause delays in project construction, large amounts of waste generated after construction, cost overruns during construction, and other problems caused by a lack of accuracy and poor coordination that can disrupt the productivity of construction projects. As technology develops, Building Information Modeling (BIM) is use as a solution to overcome various problems in the construction sector with a system that can collect and manage important data in the construction planning process that is integrated into accurate 3D modeling. In this final project, Building Information Modeling (BIM) will be used to plan the 6-floor Flats of the Ministry of Social Affairs BBRSPDF Surakarta City. Outputs be generated can be in the form of superstructure and substructure plans, namely the design of foundation structures, columns, beams, and plates, 2D Detail Engineering Design (DED), 3D modeling, and construction management plans in the form of Budget Plans, and scheduling.